Theological Reflections on the Narrative of Kieślowski’s Television Series Dekalog - BOGNÁR, László (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2026)
This study examines the relationship between Krzysztof Kieślowski’s television series Dekalog and the biblical Ten Commandments, whose extra-diegetic position raises the question of the title’s theological legitimacy. It challenges the assumption that the series was influenced by Tadeusz Żychiewicz’s contemporary work on the Decalogue and instead proposes a non-legalistic, non-deontic interpretation in which the commandments appear as expressions of freedom grounded in divine love and covenantal trust. Drawing on interdisciplinary theological and philosophical sources, the study highlights convergences across Jewish, Catholic, and Protestant traditions. It argues that the liberating character of the Decalogue is reflected in the narrative’s openness and in its address to the viewer as a free agent. The analysis of selected episodes – especially One, Two, and Ten – demonstrates how the series integrates the Decalogue as a horizon of freedom, a reading further supported by Kieślowski’s later work and the socio-political context of the series’ production.